Medicinal Cannabis Prescribing: A Study of Boundary Work and Medico‐Legal Risk. Issue 6 (3rd August 2021) - Case, Paula
Abstract: The prescription of 'unlicensed' cannabis‐based medicines was legalised in 2018. A 'boundary work' analysis of the post reform guidance issued for doctors reveals a discourse which frames the prescription of medicinal cannabis as a matter for clinical judgement, but also as fraught with medico‐legal hazard. The article highlights a triad of rhetorical devices comprising the 'last resort' principle, 'personal responsibility' and the randomised controlled trial as an exclusive measure of 'safety and efficacy'. Having identified a pronounced signalling of medico‐legal risk which is likely to have a chilling effect on prescribing, this article explores how the Bolam‐Bolitho formulation of the legal standard of care in negligence litigation might respond to this new domain of prescribing. This article concludes with observations about the compatibility of innovative prescribing of unlicensed cannabis medicines with the standard of care in negligence law, notwithstanding the extreme caution inherent in the interim prescribing guidance.